The use of silicon in controlling osmotic stress and its effect on seed germination characteristics and seedling growth of Camelina - Nasrin Teimoori; Mokhtar Ghobadi; Danial Kahrizi (علوم و فناوری بذر ایران, 2023)
Camelina oilseed has a lot of ability to be placed in the cultivation pattern of Iran's drylands. The seed germination and seedling establishment in dryland agriculture are usually exposed to drought stress. The aim of this study is to investigate the application effect of silicon concentrations in improving the seed germination characteristics and seedling growth of camelina under drought-stress conditions. The experiment was conducted as a factorial based on CRD with three replications at the seed laboratory of Razi University. The factors include camelina genotypes (Sohail and Line-84), drought stress (0, -3, -6, -9 bar using PEG-6000) and silicon (0, 2, 4, 6 and 8 mM using sodium silicate). According to the results, increasing the drought stress decreased the seed germination characteristics and the seedling growth. However, germination percentage, germination rate, seedling length, seedling dry weight, seedling vigor indices and allometric coefficient of plumule to radicle weight were increased by silicon. To increase the measured traits, silicon 6 and 8 mM were better than other concentrations. In general, silicon was effective in mitigating the effects of drought stress on the seedling growth of camelina by improving the seed germination characteristics and seedling growth. Therefore, it seems that the silicon is an effective factor in such studies and its usability in camelina seed technology and seed coating for dryland areas.